Preventing mental health problems in children: the Families in Mind population-based cluster randomised controlled trial - Hiscock Harriet; Bayer Jordana K; Lycett Kate; Ukoumunne Obioha C; Shaw Daniel; Gold Lisa; Gerner Bibi; Loughman Amy; Wake Melissa (BMC, 2012)
Abstract Background Externalising and internalising problems affect one in seven school-aged children and are the single strongest predictor of mental health problems into early adolescence. As the burden of mental health problems persists globally, childhood prevention of mental health problems is paramount. Prevention can be offered to all children (universal) or to children at risk of developing mental health problems (targeted). The relative effectiveness and costs of a targeted only versus combined universal and targeted approach are unknown. This study aims to determine the effectiveness, costs and uptake of two approaches to early childhood prevention of mental health problems ie: a Combined universal-targeted approach, versus a Targeted only approach, in comparison to current primary care services (Usual care). Methods/design Three armed, population-level cluster randomised trial (2010-2014) within the universal, well child Maternal Child Health system, attended by more than 80% of families in Victoria, Australia at infant age eight months. Participants were families of eight month old children from nine participating local government areas. Randomised to one of three groups: Combined, Targeted or Usual care. The interventions comprises (a) the Combined universal and targeted program where all families are offered the universal Toddlers Without Tears group parenting program followed by the targeted Family Check-Up one-on-one program or (b) the Targeted Family Check-Up program. The Family Check-Up program is only offered to children at risk of behavioural problems. Participants will be analysed according to the trial arm to which they were randomised, using logistic and linear regression models to compare primary and secondary outcomes. An economic evaluation (cost consequences analysis) will compare incremental costs to all incremental outcomes from a societal perspective. Discussion This trial will inform public health policy by making recommendations about the effectiveness and cost-effectiveness of these early prevention programs. If effective prevention programs can be implemented at the population level, the growing burden of mental health problems could be curbed. Trial registration ISRCTN61137690